Chromosomal instability in patients with Fanconi anemia from Serbia - Ćirković, Sanja; Guć-Šćekić, Marija; Vujić, Dragana; Mićić, Dragan; Škorić, Dejan (Vojnosanitetski pregled, 2014)
Background/Aim. Fanconi anemia (FA) is a rare hereditary disease in a heterogeneous group of syndromes, so-called chromosome breakage disorders. Specific hypersensitivity of its cells to chemical agents, such as diepoxybutane (DEB), was used as a part of screening among patients with clinical suspicion of FA. The aim of this study was to determine chromosomal instability in patients with FA symptoms in Serbia. Methods. A total of 70 patients with phenotypic symptoms of FA, diagnosed at the Mother and Child Health Care Institute of Serbia “Dr Vukan Čupić”, Belgrade and University Children’s Hospital, Belgrade from February 2004 to September 2011, were included in this study. Cytogenetic instability analysis was performed on untreated and DEB-treated 72 h-cultures of peripheral blood. Results. Ten patients in the group of 70 suspected of FA, showed increased DEB induced chromosome breakage and were classified into the FA group. The range of DEB induced aberrant cells percentages in the FA group was from 32% to 82%. DEB sensitivity of 58 tested patients were bellow FA values (range: 0–6%) (non-FA group), with no overlapping. The remaining two patients showed borderline sensitivity (borderline FA group – FA*), comparing to the healthy controls. Conclusion. This study revealed 10 patients with FA on the basis of cytogenetic analysis of DEB induced chromosome aberrations. Our results are in consistency with those from the literature. Early and precise diagnosis of FA is very important in further treatment of these patients, considering its cancer prone and lethal effects.